Pegadaian Transformation In Meeting Customer Needs Based On Sharia Finance - Musthafa Syukur; Maudy Sulis Setyaningsih; Ismi Lailiyatil Wardah; Ana Sri Wulandari; Rifqoh Maulidah (Assets Journal: Journal of Economic and Business, 2024)
In this article will be explained about the pegadaian shariah and its legal basis in the Fatwa DSN-MUI. Gadai in Islam is also referred to as rahn, which means to handle a good as a guarantee on the debt transactions carried out with the principle of Shariah. This is a solution for society to meet its urgent financial needs. The transformation of custody practices in Indonesia is growing very rapidly with the increasing need of people for fast funds to meet their basic needs. This factor inspired a number of sharia banks and key words of government agencies to open mortgage services in their place.